Inteligent clustrering withPCA and unsupervised learning algorithm in intrusion alert correlation - Siti Zaiton Mohd. Hashim, author; Maheyzah Sirat @ Md. Siraj, 1977-, author; Mohd. Aizaini Maarof, author; International Conference on Information Assurance & Security (5th: 2009: China) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL